Zonisamide for the Efficacy of Sleep Abnormality in Parkinson's Disease (ZEAL Study): A Protocol for Randomized Controlled Trials - Kataoka, Hiroshi; Isogawa, Masahiro; Inoue, Takashi; Hasebe, Miyoko; Takashima, Ryuzo; Kasama, Shu; Nanaura, Hitoki; Kiriyama, Takao; Kasahara, Masato; Sugie, Kazuma (Frontiers in Neurology, 2021)
Background Sleep disorders are one of the most frequent non-motor symptoms of Parkinson’s disease (PD), and the efficacy of dopaminergic agents remains controversial. Clinical randomized control trials for the treatment of sleep disorders in PD are limited. Zonisamide (1,2‐benzisoxazole‐3‐methanesulfonamide) improved motor symptoms and wearing-off in patients with PD. Patients with PD were reported to have dream-enacting behavior that resolved after treatment with zonisamide. The aim of this study was to verify the safety and efficacy of zonisamide for sleep disorders and rapid eye movement (REM) sleep behavioral disorders using a mobile two-channel electroencephalography (EEG)/electrooculography (EOG) recording system. Methods and analysis The present study was a randomized placebo-controlled trial to determine the efficacy of zonisamide for sleep disorders in patients with PD. This study was designed to be single-blind, but the subject allocation was randomized by an independent allocation manager via computer-generated block randomization. The subjects in the treatment group took zonisamide (25 mg per day) before bedtime for 28 days. The sleep index was analyzed using a portable EEG/EOG recording system collected on two consecutive nights within 7 days prior to the intervention and reobtained on one night within 2 days after the 28-day administration of zonisamide. The amount of change in sleep efficiency before and after the 28-day administration will be compared between the zonisamide treatment group and placebo group with respect to the primary endpoint. As for the secondary endpoint, the change in the ratio of other sleep parameters, including REM sleep without atonia, or sleep architecture will be evaluated. Ethics and dissemination: The protocol was approved by the Nara Medical University Certified Review Board (CRB5200002). The trial was notified and registered with the Japan Registry of Clinical Trials (jRCTs051200160). Written informed consent will be obtained from every participant using informed consent approved by the CRB. The results of this trial will be disseminated through peer-reviewed scientific journals.